Performa dan Determinan Petani dalam Keputusan Adopsi Inovasi Sistem Tanam Padi Rawa di Sumatera Selatan - Dessy Adriani; Elisa Wildayana; Idham Alamsyah; Amruzie Minha (Research Center for Sub-optimal Lands (PUR-PLSO), Universitas Sriwijaya, 2019)
Adriani D, Wildayana E, Alamsyah I, Minha A. 2019. Performance and determinants of farmers in adoption decision of innovation for swamps rice cropping system in South Sumatra. Jurnal Lahan Suboptimal: Journal of Suboptimal Lands. 8(2):181-191. The development of food crops in swamplands became one of main focus of the government in the development of rice farming in Indonesia. A variety of ecological constraints that accompany the development of agriculture in swamp land overcome by a variety of technological innovations, one of which is with the application of Cropping Index 200 (CI 200) technology. After nearly 5 years of CI 200 technology applied on swamp land is considered necessary for analysis related to the performance of socio-economic of farmers in the adoption of technology innovations CI 200. This study aimed to analyze the socio-economic condition of farmers in adopting IP 200 technology innovation, and analyze the determinants of IP 200 technology adoption decisions. Research was using the survey method and has been carried out in 2 districts, namely Tanjung Lago sub-District, Banyuasin District and Pemulutan sub-District, Ogan Ilir District in June-July 2019. Sampling method used disproportionate stratified random sampling. The analysis of the data was using tabulations, mathematical and logistic regression analysis. The results of the analysis showed that there were differences in the performance of the socioeconomy of farmers adopting and not adopting. The performance of the socio-economic of farmers who adopt were better than farmers who did not adopt the technology CI 200. The factors that determine the farmers adopt were the age, education, origin, experience, income, and the cost of farming.